Observation and Improvement to Undergraduate Student Activities in English Skill Using Mobile-Assisted Language Learning - Setiyanti, Anis; Basit, Abd.; Suharsiwi, Suharsiwi (English Language in Focus (ELIF), 2022)
Language plays an important role in social life because it is more than just a series of sounds that can be empirically digested, but it is also rich in meaning. In Indonesia, English is one of the subjects taught in universities. Speaking activity is a communicative event that includes the use of both verbal and nonverbal language to convey meaning. Speaking is the process of constructing and sharing meaning through the use of verbal and nonverbal symbols in various contexts. The method of data collection and interpretation used by researchers in this study is guided by the model proposed by Kemmis and McTaggart, which includes planning for a change (planning a change), actions and observations of the process and the consequences of the process (acting and observing the process and the consequences of the charge), and reflecting on the processes.  The implementation of the first cycle or cycle I, which has implemented learning using the Mobile Assisted Language Learning (MALL) method, students are able to describe something when speaking English with the material provided by the researcher. After the action was given in the first cycle, the results showed that, in general, the average score of students' scores had increased but had not yet reached the minimum target score that was defined at the beginning of the study, which was 75 percent of the total score obtained by students.